A Survey of Enterobacteriaceae and Resistance of Greater Rhea (Rhea Americana) Eggs to Experimental Contamination by Salmonella Enteritidis. (February 2017) - Cervi, Renato Clini; Andrade, Maria Auxiliadora; Minafra-Rezende, Cíntia Silva; Café, Marcos Barcellos
Eggs have protective structures against possible contamination by bacteria and fungi. Pathogenic bacteria such as Salmonella spp. are therefore rarely found in adequate sanitary conditions. Few studies about the contamination of ratite eggs have been reported, and although some studies have focused on ostrich eggs, there is no information about Greater Rhea ( Rhea americana ) eggs. The microorganisms that contaminate ratite eggs do not differ from those that affect other bird species. The purpose of this study was to characterise contamination in 16 eggs, supplied by a commercial breeding facility, by Enterobacteriaceae contamination and to assess the in vitro resistance to experimental contamination by Salmonella Enteritidis using analytical tests following the guidelines of the Georgia Poultry Laboratory. These elements are critical to the storage period, quality and physicochemical parameters. The results revealed the presence of the genera Proteus, Klebsiella, Citrobacter and Enterobacter related to the location of nests. Greater Rhea eggs were also found to be highly resistant to experimental infection by Salmonella Enteritidis.